The Leadership of the Madrasah Principal in Empowering Education Personnel - Mohammad Zaini (International Journal of Educational Sciences and Development, 2023)
The aim of this research is to determine the leadership of the madrasa head in empowering educational staff at Madrasah Aliyah Negeri 2 Malang City. The research method used is a qualitative research approach.The data collection procedure used in this research is: Participant Observation. in-depth interviews (in deep interviews), and Documentation. This research uses a case study design, The Head of MAN 2 Malang City really understands the strategic position he holds, namely as an educator, leader, organizer, innovator, manager and supervisor. These roles are then manifested in efforts to empower educational staff in MAN 2 Malang City, namely: a) madrasah/school principals provide opportunities for educational staff to improve their profession through upgrading, training, seminars and workshops, b) madrasah/school principals provide encouragement and opportunities for educational staff to continue their studies, c) madrasa/school principals pay attention to the planned need for educational staff clearly, d) madrasa/school principals provide motivation for educational staff to increase their work productivity, e) pay attention to the welfare of educational staff, f) implement cooperation with educational staff and companies or other institutions in implementing madrasa/school programs, g) fostering the discipline of educational staff.